Transpresentation of interleukin 15 by stromal cell subsets regulates immune cell homeostasis - Stecher, Carmen; Bischl, Romana; Potzmann, Elisabeth; Schmid-Böse, Anna; Ferstl, Stefanie; Braun, Nina; Richie, Ellen R.; Farlik, Matthias; Flavell, Richard A.; Herndler-Brandstetter, Dietmar (Frontiers in Immunology, 2026)
Stromal cells are important bone marrow (BM) niche components that regulate immune cell homeostasis through the production of cytokines such as interleukin 15 (IL-15). Although stromal-derived IL-15 is known to support lymphocyte survival, it remains unclear which stromal cell subsets are capable of IL-15 transpresentation, and how they influence specific lymphocyte populations. By using conditional IL-15 receptor alpha (IL-15Rα) deletion models, we demonstrate that IL-15Rα expression by BM stromal cells is essential for the maintenance of multiple IL-15-dependent lymphocyte populations. Deletion of IL-15Rα in Lepr+ or IL-7+ stromal cells selectively reduced central memory CD8+ T cells in the BM, whereas deletion of IL-15Rα in Osx+ stromal cells resulted in a marked loss of natural killer T (NKT) cells and tissue-resident memory CD8+ T cells. Surprisingly, endothelial-specific IL-15Rα deletion did not affect lymphocyte maintenance in the BM, but specifically impaired natural killer (NK) maturation and survival in the periphery, uncovering a role of endothelial IL-15 in mature NK cell maintenance. Together, our findings establish that transpresentation of IL-15 by distinct BM stromal cell subsets creates functionally specialized BM niches to support specific lymphocyte populations.